Evaluation of bacterial nanocellulose membranes loaded or not with nisin as a complementary treatment in surgical dehorning wounds in bovines - Custódio, Fábio A. F.; de Castro, Leonardo M.; Unterkircher, Erick; Porto, Ana Carolina R. C.; Braga, Iolanda S. [UNESP]; Hataka, Alessandre [UNESP]; Jozala, Angela F.; Grotto, Denise (MDPI, 2021)
Treatments of postsurgical dehorning in cattle usually includes topical application of healing agents in wounds. The Bacterial Nanocellulose (BNC) may come to a complementary treatment for these wounds. Two new complementary treatments with BNC and BNC loaded with nisin were evaluated for wound healing in surgical dehorning in bovine. Hence, two groups of experiments were run, and 12 animals were used in each group. All animals, in right and left horns, received antisepsis treatment. For the first group, the left horn was the control, and on the right one the BNC was applied. For the second group, BNC was applied on the left horn (control) and on the right ones BNC+nisin was applied. In both experiments, wounds were evaluated macroscopically by photographic images and microscopically by histology. For macroscopic evaluations, a significant difference was observed over time, but only in the comparison within the same groups. Microscopic analyzes did not showed significant differences in any type of comparison. In conclusion, there was a clinical improvement in the wound healing response with the application of BNC. However, there was no significant difference between BNC compared to the nisin loaded in BNC. For the first time it was applied a BNC in surgical dehorning wounds in bovines and evaluated the efficacy of treatment in a real animal handling situation.
Keywords: Bacterial nanocellulose; Dehorning; Dressing; Nisin; Veterinary medicines; Wound healing